Radiologic and pathologic characteristics of myeloperoxidase-antineutrophil cytoplasmic antibody-associated interstitial lung disease: a retrospective analysis - Baqir, Misbah; Yi, Eunhee; Colby, Thomas; Cox, Christian; Ryu, Jay; Specks, Ulrich (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2019)
Background: The association between interstitial lung disease (ILD) and myeloperoxidase (MPO)-antineutrophil cytoplasmic antibodies (ANCAs) has been described, but pathologic characteristics are not well characterized. Objectives: We assessed the radiologic and pathologic characteristics of ILD in MPO-ANCA–positive patients and the association between ILD and vasculitis, particularly microscopic polyangiitis (MPA). Methods: We retrospectively searched electronic health records to identify MPO-ANCA–positive patients with ILD who underwent surgical lung biopsy at our institution from January 1997 through August 2017. Demographic, clinical, imaging, and pathologic characteristics were analyzed. Results: We identified 18 MPO-ANCA–positive patients with ILD. The median (range) age was 58 (43-75) years, and the cohort included 10 men (56%), 10 former smokers (56%), and 11 patients (61%) had clinical evidence of systemic vasculitis (MPA) at the time of diagnosis of ILD. On high-resolution computed tomography, the most common radiologic pattern was “inconsistent with usual interstitial pneumonia” (UIP) (n=14 [78%]); the other 4 patients (22%) fulfilled the radiologic criteria for the UIP pattern. Honeycombing was seen in 15 patients (83%). Ten patients (56%) had the UIP pattern on biopsy: 4 of these patients had additional inflammatory changes that were not typical of UIP (as seen in patients with idiopathic pulmonary fibrosis), and the other 6 patients had other inflammatory patterns or findings. The presence or absence of MPA did not correlate with pathologic findings. Conclusions: MPO-ANCA–positive patients with ILD do not show the typical UIP pattern as seen in patients with idiopathic pulmonary fibrosis on surgical lung biopsy.